The innovation system in Bolivia: Overall perspectives - Carlos Aguirre Bastos; Francisco Javier Aliaga (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2014)
"Closing the Loop" is a project that focuses on the expectations that are linked not only to the role of science, technology and innovation (STI) in development but also to its results. Its goals are to increase the relevance and utilization of research outputs, thereby enhancing the influence of researchers, organizations and institutions on the development process. The project looks, through case studies, at the research landscape and national and sector innovation system in four countries: Bolivia, Mozambique, Tanzania and Vietnam. This contribution analyses the case of Bolivia.
Keywords: 330